Efektivitas Diskusi Kelompok Buzz Group dalam Pembelajaran Inquiry untuk Meningkatkan Pemahaman Konsep IPA Siswa MI Noor Mushola Surabaya: Penelitian - Wedar Putri Solehati; M. Amin; Hanik Yuni Alfiyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to evaluate the effectiveness of the Buzz Group discussion method in inquiry-based learning to improve students' understanding of science concepts at Madrasah Ibtidaiyah Noor Mushola Surabaya. A quantitative methodology with a quasi-experimental design was employed, involving 56 students from classes IV A and B, with results indicating a significant difference in concept understanding between the experimental and control groups. Analysis results showed that the average post-test score for the experimental class reached 78.93, while the control class scored only 54.29. The implementation of Buzz Group enhanced concept understanding with an N-Gain value of 61.41%, compared to 27.60% in the control class, indicating that the integration of this method is effective in building better understanding among students. This research highlights the importance of active and collaborative teaching methods to address the challenges of low science comprehension at the elementary level.